Leukemias associated with neurofibromatosis in children - Gürgey, Aytemiz; Hiçsönmez, Gönül; Balcı, Sevim; Ertürk, Gülyüz; İrken, Gülersu (The Turkish Journal of Pediatrics, 1987)
Five patients with leukemia associated with neurofibromatosis are presented. All the patients had café-au-lait spots, a classic feature of neurofibromatosis. Three patients had juvenile-type chronic myelocytic leukemia and two acute lymphoblastic leukemia.
Keywords: acute lymphoblastic leukemia; chronic myeloid leukemia; neurofibromatosis